2017
DOI: 10.1080/02640414.2017.1346274
|View full text |Cite
|
Sign up to set email alerts
|

The association between COMT rs4680 and 5-HTTLPR genotypes and concussion history in South African rugby union players

Abstract: The objective was to investigate the relationship between Catechol-O-methyltransferase (COMT) rs4680 and serotonin-transporter-linked polymorphic region (5-HTTLPR) genotypes with concussion history and personality traits. Rugby players ("all levels": n = 303), from high schools ("junior", n = 137), senior amateur, and professional teams ("senior", n = 166), completed a self-reported concussion history questionnaire, Cloninger's Tridimensional Personality Questionnaire, and donated a DNA sample. Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…Some studies report different results such as an association of the lower expressing serotonin transporter S allele or S/S genotype of 5-HTTLPR polymorphism with extreme criminal behavior in Chinese male prisoners 76 and violent behavior in adult German criminal offenders with history of childhood ADHD 77 . Other studies also reported association of S allele or S/S genotype with antisocial alcoholism 78 , concussion history and personality traits in rugby players 79 , suicidal ideation in acute coronary syndrome patients 80 , higher impulsivity, hostility and neuroticism in anxiety phenotype 81 , hyperactivity-impulsivity in children moderated by peer problems earlier in childhood 82 and increased exposure to life stressors moderated by ADHD symptoms early in life 83 . Some meta-analyses also describe association of low expression allele/genotype of 5-HTTLPR polymorphism with anti-social behavior 84 , violent suicide attempts 85 and bipolar disorder 86 .…”
Section: Discussionmentioning
confidence: 92%
“…Some studies report different results such as an association of the lower expressing serotonin transporter S allele or S/S genotype of 5-HTTLPR polymorphism with extreme criminal behavior in Chinese male prisoners 76 and violent behavior in adult German criminal offenders with history of childhood ADHD 77 . Other studies also reported association of S allele or S/S genotype with antisocial alcoholism 78 , concussion history and personality traits in rugby players 79 , suicidal ideation in acute coronary syndrome patients 80 , higher impulsivity, hostility and neuroticism in anxiety phenotype 81 , hyperactivity-impulsivity in children moderated by peer problems earlier in childhood 82 and increased exposure to life stressors moderated by ADHD symptoms early in life 83 . Some meta-analyses also describe association of low expression allele/genotype of 5-HTTLPR polymorphism with anti-social behavior 84 , violent suicide attempts 85 and bipolar disorder 86 .…”
Section: Discussionmentioning
confidence: 92%
“…However, Lipsky et al [116] employed a battery of executive function tests including the Wisconsin Card Sorting Test, while Willmott et al [169] used the Glasgow Outcome Scale-Extended as a measure of functional outcome post-TBI. Mc Fie et al [21] reported that Met carriers in a cohort of youth and professional South African RU players were~3-fold more likely to have a history of concussion and, accordingly, it has been postulated that elevated dopamine could increase impulsivity and risk taking meaning Met allele carriers could place themselves at increased risk of sustaining a concussion [170,171].…”
Section: Catechol-o-methyltransferase Polymorphismmentioning
confidence: 99%
“…However, children and adolescents carrying the S allele showed more impulsive behaviour such as delay aversion during target-game activity [131]. Recently, it has been observed that 5-HTTLPR low (S A /S A ) and intermediate (S A /L A , S A /L G , L A /L G , L G /L G )-possessing junior RU players displayed less harm avoidance behaviour [21]. These findings suggest that genetic variants associated with personality and thus behavioural traits could influence concussion risk in rugby.…”
Section: Serotonin Transporter Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging research has also shown an association between a number of polymorphisms and the skill acquisition process [68]. Finally, a number of genetic variants have been linked to an increased susceptibility to concussion injuries [69]. As a result, whilst this information could be used to bias against those with the perceived "unfavourable" genotypes, it could also be used to personalize the training process, identifying those athletes who need greater attention in these areas.…”
Section: What Could We Potentially Use Genetic Testing For?mentioning
confidence: 99%